Thermostimulated luminescence and the temperature dependence of X-ray luminescence of the Li₂B₄O₇ single crystals - Hunda, B.M.; Puga, P.P.; Solomon, A.M.; Holovey, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The copper-doped lithium tetraborate (Li₂B₄O₇:Cu) is one of the famous tissue-equivalent materials for the thermoluminescent dosimetry, being characterized by a high radiation resistivity, a linear dose dependence, a wide operation dose range and a weak dependence of the dose on the ionizing radiation energy. We have performed the thermo-stimulated luminescence (TSL) studies of the lithium tetraborate single crystals doped with different copper concentrations. The optimal dopant concentration (1.91⋅10⁻³ weight % Cu) at which the maximum TSL intensity of the high-temperature maximum is revealed has been found. It has been elucidated that the further copper concentration increase results in the TSL intensity decrease due to the concentrational damping luminescence. It has been found that for the Li₂B₄O₇ single crystals with the optimal Cu dopant concentration within the temperature range under study TSL is primarily due to the carriers deliverance from two local trapping levels with the Et₁= 0.90 ± 0.03 eV, Et₂ = 1.72 ± 0.07 eV energies and the frequency factors of 4⋅10¹⁰ s⁻¹ and 5⋅10¹⁶ s⁻¹, respectively. The occurrence of these local levels affects considerably the temperature dependence of X-ray luminescence. Above 215⁰C the temperature damping of luminescence is observed being well described by the Mott formula with the EA = 0.65 ± 0.05 eV activation energy.